Stanley Walsh interviewed by Hazel de Berg in the Hazel de Berg collection - Walsh, Stanley, 1937-; De Berg, Hazel, 1913-1984. (1974)
Walsh, playwright, actor and director of theatre, speaks of his plays and his association with the Music Hall Theatre ; of his writing career ; acting at the Old Tote Theatre ; about his method of writing ; his views on Music Hall melodrama.
Digital master available
Transcript available (35 p.)
Keywords: Walsh, Stanley, -- 1937- -- Interviews; Actors -- Australia -- Interviews; Dramatists, Australian -- Interviews